Вільнорадикальні процеси в організмі свиней під дією біологічно активних добавок - Бучко, Оксана; Buchko, Oksana (Східноєвропейський національний університет імені Лесі Українки, 2015)
Біологічно активна добавка «Гумілід» у комплексі з аскорбіновою кислотою викликає гальмування вільно- радикальних процесів (зниження вмісту гідропероксидів ліпідів, карбонільних груп протеїнів і ТБК-активних продуктів) та стимулювання системи антиоксиданого захисту (підвищення активності супероксиддисмутази й каталази) в крові свиноматок та новонароджених поросят.The paper deals with the problem of increasing of high performance animal’s adaptive ability under the intensive technologies in the most critical moments – farrowing, lactation and birth. The influence of dietary food supplements «Humilid» with ascorbic acid on the free radical processes and antioxidant system parameters of lactating sows and their piglet’s blood in the period from birth to 21 days have been studied. It has been shown that the using of feed supplements causes by reducing of lipid hydroperoxides concentration, protein carbonyl groups and TBA-active products, increasing of superoxide dismutase and catalase activities in the blood of animals compared to control group. It has been concluded that «Humilid» in the complex with vitamin C increases adaptive ability of the sows and their newborn piglets. These supplements characterized by antistress modulating properties and prolonged effect.
Free Radical Processes in the Pig’s Organism Under the Influence of the Biologically Active Supplements
Keywords: свиноматки; поросята; критичні періоди онтогенезу; адаптаційна здатність організму; «Гумілід»; аскорбінова кислота; sows; piglets; critical periods of ontogenesis; adaptive ability of organism; «Humilid»; ascorbic acid